La reforma constitucional de 1860: la necesidad de reformar la Constitución liberal de 1856 - Jiyagón Villanueva, José Carlos (2018)
The twilight of the National Convention in 1857 marks the political change made by the government of Gen. Ramon Castilla, who assumed a policy of exclusion towards the liberal sectors. In order to carry out this change, the constitution of 1856 (product of the liberalism) was observed. A conservative campaign began to implement a constitutional reform, pointing out a series of errors found in the constitution, which demonstrated the need to reform it